2006
DOI: 10.1002/pmic.200500142
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional proteomics of human serum using parallel chromatography of native constituents and microplate technology

Abstract: A versatile, multidimensional, and non-denaturing proteome separation procedure using microplate technology is presented, yielding a digitized image of proteome composition. In the first dimension, the sample under study is separated into 96 fractions by size exclusion chromatography (SEC). In the second dimension, the fractions of the first dimension are transferred by the liquid-handling device CyBi-Well (CyBio AG, Jena, Germany) to 96 parallel anion exchange chromatography columns. In this way the proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…Schizophrenia was quantitatively compared to control samples at the level of digested peptides (Levin et al, 2007;Levin et al, 2009). Multidimensional chromatography identified 32,288 peptides matching 2,669 serum proteins and revealed that alpha1B-glycoprotein, cysteine-rich secretory protein and an apparently low molecular-weight albumin were markers of severe inflammation (Horn et al, 2006;Rozet et al, 2006;Baum et al, 2008;Kreusch et al, 2008).…”
Section: Partition Chromatography Of Proteins and Peptidesmentioning
confidence: 99%
“…Schizophrenia was quantitatively compared to control samples at the level of digested peptides (Levin et al, 2007;Levin et al, 2009). Multidimensional chromatography identified 32,288 peptides matching 2,669 serum proteins and revealed that alpha1B-glycoprotein, cysteine-rich secretory protein and an apparently low molecular-weight albumin were markers of severe inflammation (Horn et al, 2006;Rozet et al, 2006;Baum et al, 2008;Kreusch et al, 2008).…”
Section: Partition Chromatography Of Proteins and Peptidesmentioning
confidence: 99%
“…However, much progress has been made in this area. Horn et al [49] presented a high-throughput procedure for proteome research of native constituents. Human serum sample was first separated with SEC column in a mild condition and collected in a 96-well microplate.…”
Section: Chromatography Array Technologymentioning
confidence: 99%
“…The first separation step and analysis of the resulting fractions are described in [11]. Briefly, a mixture of 0.9 mL serum and 0.1 mL 10 mM Tris/HCl, pH 7.4, containing 150 mM NaCl was loaded onto a HiLoad Superdex TM 200 column (16/60, Pharmacia, Uppsala, Sweden) equilibrated with 10 mM Tris/HCl, pH 7.4, containing 150 mM NaCl.…”
Section: First Separation Dimension (1d): Size Exclusion Chromatograpmentioning
confidence: 99%
“…This method was adapted to human serum for searching indestructible biomarker candidates within blood samples, whereas plasma is generally preferred to serum for in-depth proteome analysis [12]. The separation protocol of [11] was improved with respect to resolution, throughput, reproducibility, robustness, and simplicity. The present paper shows the characteristics of the improved method whereas the accompanying paper describes application of the search principle to model diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation